Development of vestibular ocular reflex and gross motor function in infants with common cavity deformity as a type of inner ear malformation. (3rd April 2019) - Kaga, Kimitaka; Kimura, Yusuke; Minami, Shujiro
Abstract: Background： The function of common cavity deformity demonstrated by temporal bone CT and MRI has been unknown. Aim/Objective: To investigate the developmental changes of vestibular ocular reflex and acquisition of postural control in infants with common cavity deformity. Material and methods: Eight infants who were congenitally deaf complicated by common cavity deformity were studied. The damped rotational chair test was carried out to evaluate vestibular ocular reflex. Acquisition of head control and independent walking in these infants was compared with that in normal infant's milestones of gross motor development. Results : All of the eight infants with common cavity deformity did not show per-rotatory nystagmus in the damped rotational chair test around the first year of life. However, a normal number of beats and a longer duration of per-rotatory nystagmus for their age were recorded at around three or four years of age. Conclusions and significance: In the eight infants with common cavity deformity, vestibular ocular reflex was not present around the first year of life, but appeared after three or four years probably because of some vestibular sensory cells. Head control and independent walking were delayed but eventually acquired by the central vestibular compensation.